The relationship between organizational culture and Organizational Citizenship Behaviour (OCB) at Petronas Penapisan (Melaka) Sdn Bhd / Muhammad Nashriq Izmer Mohd Paizal and Nur Ain Syamimie Abd Ghani - Mohd Paizal, Muhammad Nashriq Izmer; Abd Ghani, Nur Ain Syamimie (Faculty of Business and Management, 2013)
In recent years, the employers' expectations have witnessed an upward trend, in anticipation of certain discretionary behaviors out of their employees, which fall beyond the scope of workplace requirement and reward systems. All this actually is to ensure long service periods and bring out the ‘Organizational Citizen’ within the employee in the organizational context. Organizational Citizenship Behavior (OCB) is presumed as one of the emerging management concepts that are being emphasized for the organizational effectiveness. This study aims to explore OCB and its significance for the organizations in present scenario. The present paper is an attempt to examine and investigate the relationship between Organizational Citizenship Behaviour (OCB) and Organizational Culture. The study examines the relationship of selected organizational culture variables which are organizational structures, beliefs and norms, and organizational support on OCB. The data was collected from employees at Petronas Penapisan (Melaka) Sdn Bhd through questionnaires. A sample size of 135 respondents from 230 employees in population reveals that Organizational Structures and Organizational Support have significant positive relationship with OCB with r = 0.238 (p < 0.01) and 0.241 (p < 0.01) respectively as contrast with Beliefs and Norms with r = 0.167 (p > 0.05).